2007
DOI: 10.3892/ijo.30.4.1003
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of nuclear texture, histone acetylation, and MDR1 gene expression in human drug-sensitive and -resistant OV1 cell lines

Abstract: Abstract. Image cytometric study of pathological specimens or cell lines has suggested that epigenetic mechanisms are likely to play a major role in determining chromatin patterns evaluable through nuclear texture analysis. We previously reported that nuclear textural changes observed in the OV1-VCR etoposide-resistant ovarian carcinoma cell line were associated with an increased acetylated histone H4 level. In this study we analyzed the effects of treatments with the HDAC inhibitor trichostatin A (TSA) or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 30 publications
3
34
0
2
Order By: Relevance
“…Considerable experimental evidence suggests that histone acetylation and DNA methylation are involved in this control (16)(17)(18)(19). Consistent with these and other previous studies we also observed that treatments which modulate nuclear architecture could result in ABCB1 up-or down-regulations in various tumour cell lines (3,10,11).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Considerable experimental evidence suggests that histone acetylation and DNA methylation are involved in this control (16)(17)(18)(19). Consistent with these and other previous studies we also observed that treatments which modulate nuclear architecture could result in ABCB1 up-or down-regulations in various tumour cell lines (3,10,11).…”
Section: Discussionsupporting
confidence: 80%
“…In this context, we reported previously that histone deacetylases inhibitor TSA could induce chromatin texture changes in tumour cell lines (H69, OV1) and that this effect could, in some cases, be associated with ABCB1 gene expression regulations (10,11). Previous studies indicate that thalidomide could also play a role on drug-resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ABCB1 promoter of H69VP cells is constitutively strongly hypomethylated, and the downregulation of ABCB1 expression by HDAC inhibition could require such low level of DNA methylation in ABCB1 promoter. Indeed, we have previously shown that ABCB1 expression remains unchanged after TSA treatment of the multidrug-resistant human ovarian adenocarcinoma cell line OV1/VCR, in which ABCB1 promoter is slightly hypermethylated compared to its sensitive IGROV1 counterpart (Yatouji et al, 2007). Further methylation analysis on different cell lines and clinical samples is required to clarify the relevancy of basal methylation status of ABCB1 promoter on ABCB1 repression by HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 98%